Temporal course of attention bias toward emotional faces in individuals with autistic traits: an eye-movement study - Meng, Chunyan; Li, Taolin; Wang, Jing (Frontiers in Neuroscience, 2023)
Introduction Similar attention patterns have been found in individuals with autism spectrum disorder (ASD) and autistic traits (ATs). The Intense World Theory and previous studies suggest that individuals with ASD may demonstrate a vigilance-avoidance attention pattern toward emotional faces. However, the attention patterns in individuals with ATs remain unclear. Therefore, this study employs eye-tracking technology to examine the characteristics and temporal course of attention bias toward emotional faces in individuals with ATs. Methods The Autism-spectrum Quotient (AQ) was used to evaluate the level of ATs among 2,502 college students. A total of 50 participants were selected from the 2,502 college students: 25 high-AQ group participants were randomly selected from the 10% of individuals with the highest AQ scores. Similarly, 25 low-AQ group participants were randomly selected from the 10% of participants with the lowest AQ scores. All selected participants completed an eye-tracking study while performing a dot-probe task with emotional faces (positive-neutral, negative-neutral, and negative–positive). By analyzing data from different time periods, the attention bias and time course of individuals with ATs toward emotional faces were investigated. Results The results show that compared to the low-AQ group, the high-AQ group detected negative faces faster in the early stages of emotional face processing. As the presentation time of emotional faces increased (at the 2–3 s mark), the fixation scores for negative-neutral faces of the high-AQ group were less than 0.5, which was significantly lower than those of the low-AQ group. Meanwhile, the high-AQ group showed brief attentional avoidance toward positive emotion at 3–4 s in the positive-neutral trials, indicating that the high-AQ group exhibited attention avoidance to both negative and positive faces during the middle and later stages of emotional processing. Conclusion This study suggests that individuals with ATs display a vigilance-avoidance pattern toward emotional faces. It contributes to a deeper understanding of the mechanisms of attention in persons with ATs and further supports the Intense World Theory.